Nutrient supplementation for prevention of viral respiratory tract infections in healthy subjects: A systematic review and meta‐analysis - Vlieg‐ Boerstra, Berber; Jong, Nicolette; Meyer, Rosan; Agostoni, Carlo; De Cosmi, Valentina; Grimshaw, Kate; Milani, Gregorio Paolo; Muraro, Antonella; Oude Elberink, Hanneke; Pali‐ Schöll, Isabella; Roduit, Caroline; Sasaki, Mari; et al. (Allergy (Copenhagen), 2022)
It remains uncertain as to whether nutrient supplementation for the general population considered healthy could be useful in the prevention of RTIs, such as COVID‐19. In this systematic review and meta‐analysis, the evidence was evaluated for primary prevention of any viral respiratory tract infection (RTI) such as SARS‐CoV‐2, through supplementation of nutrients with a recognized role in immune function: multiple micronutrients, vitamin A, folic acid, vitamin B12, C, D, E, beta‐carotene, zinc, iron and long‐chain polyunsaturated fatty acids. The search produced 15,163 records of which 93 papers (based on 115 studies) met the inclusion criteria, resulting in 199,055 subjects (191,636 children and 7,419 adults) from 37 countries. Sixty‐three studies were included in the meta‐analyses, which was performed for children and adults separately. By stratifying the meta‐analysis by world regions, only studies performed in Asia showed a significant but heterogeneous protective effect of zinc supplementation on RTIs (RR 0.86, 95% CI 0.7–0.96, I2 = 79.1%, p = .000). Vitamin D supplementation in adults significantly decreased the incidence of RTI (RR 0.89, 95% CI 0.79–0.99, p = .272), particularly in North America (RR 0.82 95% CI 0.68–0.97), but not in Europe or Oceania. Supplementation of nutrients in the general population has either no or at most a very limited effect on prevention of RTIs. Zinc supplementation appears protective for children in Asia, whilst vitamin D may protect adults in the USA and Canada. In 10/115 (8.7%) studies post‐hoc analyses based on stratification for nutritional status was performed. In only one study zinc supplementation was found to be more effective in children with low zinc serum as compared to children with normal zinc serum levels.